2020
DOI: 10.1038/s41598-020-75442-6
|View full text |Cite
|
Sign up to set email alerts
|

N-(2-mercaptopropionyl)-glycine enhances in vitro pig embryo production and reduces oxidative stress

Abstract: This study evaluated the effects of different concentrations (1, 10, 25, 50, and 100 µM) of the antioxidant N-(2-mercaptopropionyl)-glycine (NMPG), during the culture of in vitro-fertilized porcine oocytes. While the highest concentrations of NMPG (50 and 100 µM) were toxic to the developing embryos during the first two days of culture, 25 µM NMPG achieved cleavage rates that were similar to those achieved by the control but did not sustain blastocyst production by Day 7 of culture. Compared to the control cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The addition of antioxidants activates the development of embryos during the preimplantation process. Many studies have shown that the development of blastocysts from fertilized eggs, as well as the preimplantation of blastocytes, can be improved by the addition of antioxidant substances to the culture medium of fertilized eggs [ 10 , 11 , 12 , 13 ]. Recent studies have indicated that mesenchymal stem cells possess antioxidant properties against biological events [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of antioxidants activates the development of embryos during the preimplantation process. Many studies have shown that the development of blastocysts from fertilized eggs, as well as the preimplantation of blastocytes, can be improved by the addition of antioxidant substances to the culture medium of fertilized eggs [ 10 , 11 , 12 , 13 ]. Recent studies have indicated that mesenchymal stem cells possess antioxidant properties against biological events [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the application of antioxidants to ART can be an effective intervention to counteract the oxidative damage in in vitro-produced embryos [ 7 ], especially to improve the in vitro culture (IVC) medium for favorable outcomes in preimplantation embryo development. Accumulating studies have indicated that the addition of antioxidants to IVC medium improves preimplantation embryo development by regulating the embryonic environment and protecting embryos from oxidative damage [ 8 , 9 , 10 , 11 ], which leads to the decrease in developmental competence of embryos produced in vitro compared to that of embryos developed in vivo [ 12 ].…”
Section: Introductionmentioning
confidence: 99%